Total rhinectomy, a clinical review of nine cases. (August 2016) - Subramaniam, T.; Lennon, P.; O'Neill, J.; Kinsella, J.; Timon, C.
Abstract Introduction A large proportion of malignancies involving the external nose can be managed with limited resection and local autologous reconstruction or, in some cases, radiotherapy as primary or adjuvant treatment. We highlight a small cohort of patients undergoing total rhinectomy for advanced nasal malignancies. Methods A retrospective review of all patients undergoing total rhinectomy in our institution from 2006 to 2014 was undertaken. We reviewed patient demographics, surgical management, adjuvant treatment, histology, reconstruction and outcomes. Results Nine patients underwent total rhinectomy over an 8-year period, three of whom were being treated for recurrent disease. Eight patients had squamous cell carcinoma (SCC) and a single patient had an angiosarcoma. Two patients completed adjuvant radiotherapy. Seven patients underwent nasal prosthetic rehabilitation. All nine patients are alive and disease free at latest follow-up. Conclusion Total rhinectomy is an uncommon procedure usually undertaken for extensive nasal malignancy. Nasal prosthetic rehabilitation is a viable method of reconstruction.